O nagłówkach tekstów publikowanych na portalu Treningbiegacza.pl - Olejniczak, Elwira (Acta Universitatis Lodziensis. Folia Linguistica, 2017)
The aim of article is analysis of headlines of texts published on portal Treningbiegacza.pl. Information titles are blended with advertising and promotional. There are a lot of language games, modifications of idioms, rhetorical questions, quotes and hints and elements of specialistic vocabulary. Titles predominate motivating healthy style life and rational nutrition, taking up of challenges or shopping of concrete products. Pragmatic function is more important than information.